2013
DOI: 10.3389/fonc.2013.00175
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the AMP-Activated Protein Kinase for Cancer Prevention and Therapy

Abstract: Despite the advances in biomedical research and clinical applications, cancer remains a leading cause of death worldwide. Given the limitations of conventional chemotherapeutics, including serious toxicities and reduced quality of life for patients, the development of safe and efficacious alternatives with known mechanism of action is much needed. Prevention of cancer through dietary intervention may hold promise and has been investigated extensively in the recent years. AMP-activated protein kinase (AMPK) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 108 publications
1
111
0
Order By: Relevance
“…The results of this study revealed that Gas1 inhibited EMT and Warburg effect through the AMPK/mTOR/P70S6K pathway. Based on the decisive role of AMPK/mTOR/P70S6K on cell-cycle and nutrient sensing (34)(35)(36), in combination with our observation of the inhibitory role of Gas1 in proliferation, we speculated that Gas1 was connected to the activation of AMPK/mTOR/S6K axis and had an impact on the total and active states of AMPK/mTOR/S6K signaling pathway.…”
Section: Discussionmentioning
confidence: 84%
“…The results of this study revealed that Gas1 inhibited EMT and Warburg effect through the AMPK/mTOR/P70S6K pathway. Based on the decisive role of AMPK/mTOR/P70S6K on cell-cycle and nutrient sensing (34)(35)(36), in combination with our observation of the inhibitory role of Gas1 in proliferation, we speculated that Gas1 was connected to the activation of AMPK/mTOR/S6K axis and had an impact on the total and active states of AMPK/mTOR/S6K signaling pathway.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have also proposed AMPK as a key tumor suppressor protein [12-14]. Activated AMPK exerts anti-cancer functions via different mechanisms, including mTOR complex 1 (mTORC1) inhibition [15], autophagy induction [16], p53 activation [17], as well as degradation of several key oncogenic proteins [18, 19]. AMPK can also modulate epithelial-to-messenchymal transition (EMT) via regulating Akt-MDM2-Foxo3 signaling [20].…”
Section: Introductionmentioning
confidence: 99%
“…AMPK, a serine-threonine kinase protein complex that plays a role in the regulation of energy balance in diverse organs, is closely associated with the prevention of lifestyle-related diseases such as obesity, diabetes, and metabolic syndrome (Steinberg and Kemp, 2009). The activation of AMPK requires the phosphorylation of Thr-172 at the loops of α1 and α2 subunits by the activation of upstream kinases, including liver kinase B1 (LKB1), Ca 2 þ /calmodulindependent protein kinase kinase (CaMKK), or transforming growth factor-ß-activated kinase (TAK-1) (Hardie, 2008;Kim and He, 2013). Within our limited findings, it still remains unclear which up-stream signalling mechanism(s) are involved in the AMPK activation by theaflavins in Caco-2 cells, although the CaMKK/AMPK pathway was able to be excluded .…”
Section: Activity Of Theaflavins In the Intestinementioning
confidence: 99%